Security issues of cloud computing environment in possible military applications - Samčović, Andreja (Vojnotehnički glasnik / Military Technical Courier, 2013)
The evolution of cloud computing over the past few years is potentially one of the major advances in the history of computing and telecommunications. Although there are many benefits of adopting cloud computing, there are also some significant barriers to adoption, where the most important are security issues. This paper introduces the concept of cloud computing; looks at relevant technologies in cloud computing; takes into account some market potentials and applications as well as some cloud deployment models. Additionally, Security-as-a-Service is specially considered because of its importance in the military applications.